Etika Berbusana di Kalangan Generasi Muda - Chintya Mei Sony Nababan; Feby Adelvia Sitepu; Meysi Asma Haniyah; Salwa Fitria Naution; Silvi Nurhidayasi; Syarifah Annisa Salsabila; Jamaludin J (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to find out problems that occur regarding ethics in clothing. Ethics in dressing according to Pancasila values is also an awareness in higher education regarding morals and norms for students who will become future teachers. Apart from that, to maintain honor and a good reputation. Many students today prioritize fashion rather than good ethical values, which can be expressed in Pancasila values, which uphold good moral and ethical values. This research uses qualitative research methods or a descriptive approach. This research uses library research where researchers collect data from books, articles and journals. Previous research used data collection methods using library materials. The results of this research show the importance of ethics in the lives of today's young generation. So there is no gap in ethical clothing.